Problems of Modern Russian Teenagers’ Social Competence Development - Sorochinskaya, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The given article provides theoretical analysis of the process of modern Russian teenagers’ social competence development as part of Russian presidential initiative “Our new school”. The author gives a detailed account of the key components of the process of teenagers’ social evolution within which social competence is developed. The essence of psychological-pedagogical approach to the given process is revealed. The author analyses approaches by scientists-pedagogues to the issue under study, in particular, academicmethodical support of the given process. The conditions necessary for efficient teenagers’ social competence development are dwelt on.